Bank Bailouts, International Linkages and Cooperation - Friederike Niepmann; Tim Schmidt-Eisenlohr (Oesterreichische Nationalbank (OeNB), 2011)
On the occasion of the 65th birthday of Governor Klaus Liebscher and in recognition of his commitment to Austria's participation in European monetary union and to the cause of European integration, the Oesterreichische Nationalbank (OeNB) established a "Klaus Liebscher Award". It has been offered annually since 2005 for up to two excellent scientific papers on European monetary union and European integration issues. The authors must be less than 35 years old and be citizens from EU member or EU candidate countries. Each "Klaus Liebscher Award" is worth EUR 10,000. The winning papers of the seventh Award 2011 were written by Friederike Niepmann and Tim Schmidt-Eisenlohr (shared award) and by Steffen Osterloh. Friederike Niepmann's and Tim Schmidt-Eisenlohr's paper is presented in this Working Paper while Steffen Osterloh's contribution is contained in Working Paper 169 . In this paper Friederike Niepmann and Tim Schmidt-Eisenlohr start from the observation that financial institutions are increasingly linked internationally. As a result, financial crisis and government intervention have stronger effects beyond borders. The authors provide a model of international contagion allowing for bank bailouts. While a social planner trades off tax distortions, liquidation losses and intraand intercountry income inequality, in the non-cooperative game between governments there are inefficiencies due to externalities, no burden sharing and freeriding. The authors show that, in absence of cooperation, stronger interbank linkages make government interests diverge, whereas cross-border asset holdings tend to align them. The authors analyze different forms of cooperation and their effects on global and national welfare.
Keywords: F36; F42; G01; G28; 330; bailout; contagion; financial crisis; international institutional arrangements